Human phosphatase CDC14A regulates actin organization through dephosphorylation of epithelial protein lost in neoplasm - Chen, Nan-Peng; Uddin, Borhan; Hardt, Robert; Ding, Wen; Panić, Marko; Lucibello, Ilaria; Ruppert, Thomas; Schiebel, Elmar (Proceedings of the National Academy of Sciences of the United States of America, 2017)
CDC14 is an essential dual-specificity phosphatase that counteracts CDK1 activity during anaphase to promote mitotic exit in Saccharomyces cerevisiae. Surprisingly, human CDC14A is not essential for cell cycle progression. Instead, it regulates cell migration and cell adhesion. Little is known about the substrates of hCDC14A and the counteracting kinases. Here, we combine phospho-proteome profiling and proximity-dependent biotin identification to identify hCDC14A substrates. Among these targets were actin regulators, including the tumor suppressor eplin. hCDC14A counteracts EGF-induced rearrangements of actin cytoskeleton by dephosphorylating eplin at two known extracellular signal-regulated kinase sites, serine 362 and 604. hCDC14APD and eplin knockout cell lines exhibited down-regulation of E-cadherin and a reduction in α/β-catenin at cell-cell adhesions. Reduction in the levels of hCDC14A and eplin mRNA is frequently associated with colorectal carcinoma and is correlated with poor prognosis. We therefore propose that eplin dephosphorylation by hCDC14A reduces actin dynamics to restrict tumor malignancy.
Published first May 2, 2017
Gesehen am 27.06.2018